PENGARUH DIVIDEND PAYOUT RATIO, RETURN ON ASSET, DAN PENJUALAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sihombing, Binsar (UNIKA Santo Thomas, 2011)
This study aimed to analyze the effect of dividend payout ratio, return on assets and sales of company stock at Indonesia Stock Exchange. To achieve these objectives, sampling in this study using purposive sampling method. Population used in this study are listed manufacturing companies in Indonesia PT.Bursa Securities in 2009 as many as 153 companies, of the population taken as a sample of 42 companies. Analyses were performed with multiple linear regression models. Note that the discussion of the results, the dividend payout ratio, return on assets and sales have a positive effect on stock prices. Dividend payout ratio has a regression coefficient of 0.180311 with a probability of 0.0847 or 8.47 percent. Return on assets has a regression coefficient of 0.54029 with a probability of 0.0093 or 0.93 percent. Sedangka sales have koefien regression of 0.428178 with a probability of 0.0000, or 0 percent.